2019
DOI: 10.1021/acssuschemeng.8b06734
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Separation of Phenolic Compounds from Coal-Based Liquid Oil by Deep Eutectic Solvents

Abstract: The separation of phenolic compounds from coal-based liquid oil is of economic value and practical significance. Conventional separation techniques for phenolic compounds always produce a large amount of wastewater. Herein, deep eutectic solvents (DESs) are considered as effective alternatives to traditional solvents. To complete the separation of phenolic compounds from coal-based liquid oil, DESs should have stronger interactions with phenols than the oil and form new DES-phenol aggregates, breaking the orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Then, compared with the ionic liquid, Bet‐Gly has lower price and simpler synthesis process, and it is more suitable for industrial applications. Besides, compared with other DES that are mostly synthesized from quaternary ammonium salts containing halogen atoms, for example, choline chloride‐glycerol (extraction efficiency is 98.3%, the neutral oil entrainment is 4.2%), 33 although Bet‐Gly extraction efficiency is about 4% lower and neutral oil entrainment is similar, Bet‐Gly has no harm to steel equipment, and this is an irreplaceable advantage. Compared with the betaine that was used as solvent alone, the Bet‐Gly has a slightly larger highest extraction efficiency (94.7%) than betaine (93.0%), 29 and it reduced entrainment of neutral oil in extraction (5.2%) than betaine (14.8%) 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Then, compared with the ionic liquid, Bet‐Gly has lower price and simpler synthesis process, and it is more suitable for industrial applications. Besides, compared with other DES that are mostly synthesized from quaternary ammonium salts containing halogen atoms, for example, choline chloride‐glycerol (extraction efficiency is 98.3%, the neutral oil entrainment is 4.2%), 33 although Bet‐Gly extraction efficiency is about 4% lower and neutral oil entrainment is similar, Bet‐Gly has no harm to steel equipment, and this is an irreplaceable advantage. Compared with the betaine that was used as solvent alone, the Bet‐Gly has a slightly larger highest extraction efficiency (94.7%) than betaine (93.0%), 29 and it reduced entrainment of neutral oil in extraction (5.2%) than betaine (14.8%) 30 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, more results of separating phenolic compounds using ILs as extractants were reported in the literature. 6 , 27 29 To our knowledge, m -cresol has the highest content (13.41 wt %) in phenol oil from low-temperature coal tar, 30 but fewer literature studies have reported the separation of m -cresol as a representative phenolic compound from model oil since phenol or p -cresol is usually selected as the typical phenolic compound. 6 , 21 , 31 33 Hence, it is meaningful to explore the separation of m -cresol from LTCT by means of ionic liquids.…”
Section: Introductionmentioning
confidence: 97%
“…Catalytic hydrodeoxygenation (HDO) of phenols is a crucial process in the conversion of lignin-derived bio-oils 1–4 and coal-derived oils. 5,6 Alkylphenols, as an important class of phenolic compounds, are abundant in bio-oils 1 and coal-derived oils. The alkyl groups in alkylphenols are mainly methyl, ethyl, propyl, etc.…”
Section: Introductionmentioning
confidence: 99%